2020
DOI: 10.1038/s41598-020-78476-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of neutrophil/lymphocyte ratio and mean platelet volume/platelet ratio for 1-year mortality in critically ill patients

Abstract: Several studies have reported that the neutrophil to lymphocyte ratio (NLR) and mean platelet volume (MPV) are associated with poor prognosis. This study investigated whether NLR and/or the MPV/platelet ratio could function as predictive markers of mortality in critically ill patients. We retrospectively reviewed 1,154 patients admitted to the intensive care unit (ICU) between January 2017 and December 2017. Patients were divided into 2 groups according to 1-year mortality. We compared the NLR and MPV/platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…NLR is a reflection of physiological stress and a marker of the interaction between different immune pathways. NLR was shown to be an independent predictor of in-hospital mortality for many cardiovascular, neurovascular, and intensive-care conditions [17,18], and high NLR values can be observed in very heterogenous diseases and conditions. This is why NLR is generally considered a marker of physiologic stress among hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…NLR is a reflection of physiological stress and a marker of the interaction between different immune pathways. NLR was shown to be an independent predictor of in-hospital mortality for many cardiovascular, neurovascular, and intensive-care conditions [17,18], and high NLR values can be observed in very heterogenous diseases and conditions. This is why NLR is generally considered a marker of physiologic stress among hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…Before and independently of the COVID-19 outbreak, evidence was provided in support of the involvement of exaggerated pro-inflammatory activation of neutrophils, accompanied by the release of cytotoxic NETs, in the pathogenesis of clinical derangements present in critically ill patients ( 4 , 22 24 ). High NLR, neutrophil percentage-to-albumin ratio (NPAR), neutrophil-to-albumin ratio (NAR), neutrophil-derived enzyme myeloperoxidase, IL-8, and NETs have been reported as indicators of severe disease and poor outcomes in cardiogenic and septic shock, in acute lung injury (ALI) and acute respiratory distress syndrome (ARDS), in disseminated intravascular coagulation, and in acute kidney injury ( 22 , 25 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the value found for NRL in critically ill patients with active and inactive cancer was 21 (the 3 rd tertile). Ham et al (2020), when analyzing 1154 patients admitted to an ICU, found that the incidence of one-year mortality was significantly higher in the 3rd tertile (NLR = 24.28 ± 22.48; p < 0.001). However, this was not confirmed in our research.…”
Section: Discussionmentioning
confidence: 99%